2013
DOI: 10.3389/fimmu.2013.00039
|View full text |Cite
|
Sign up to set email alerts
|

Chronic schistosome infection leads to modulation of granuloma formation and systemic immune suppression

Abstract: Schistosome worms have been infecting humans for millennia, but it is only in the last half century that we have begun to understand the complexities of this inter-relationship. As our sophistication about the inner workings of every aspect of the immune system has increased, it has also become obvious that schistosome infections have broad ranging effects on nearly all of the innate and adaptive immune response mechanisms. Selective pressures on both the worms and their hosts, has no doubt led to co-evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 215 publications
2
54
0
3
Order By: Relevance
“…Numerous studies, reviewed in 78 , have showed an active immuneregulatory role of antibodies from infected individuals. Immune complexes from the blood of infected patients were able to inhibit in vitro granuloma formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies, reviewed in 78 , have showed an active immuneregulatory role of antibodies from infected individuals. Immune complexes from the blood of infected patients were able to inhibit in vitro granuloma formation.…”
Section: Discussionmentioning
confidence: 99%
“…In the murine model of schistosomiasis, several Th1, Th2 and Th17 as well as pro-inflammatory cytokines (such as IL-1b, IL-12 and TNF-a) regulate both granuloma formation and hepatic fibrosis 77,78 . Therefore, tight regulation of these cytokine responses generated during schistosome infection is essential to prevent excessive pathology.…”
Section: Discussionmentioning
confidence: 99%
“…As helminth infections are generally chronic, further studies are required to determine whether soluble proteins released from schistosome eggs trapped in the liver have long‐term immunomodulatory effects on the ability of hepatic cDCs to initiate and maintain adaptive immune responses. This will be particularly important for understanding the potential negative impact of helminths on immune responses to vaccines and other major pathogens that coexist in schistosome endemic areas 46 …”
Section: Discussionmentioning
confidence: 99%
“…During the chronic phase of intestinal schistosomiasis, disease morbidity has been associated mostly with the type and intensity of the granulomatous inflammatory response induced by egg‐secreting antigens that become trapped in venules in the host's tissues, especially in the liver and intestine . Granuloma formation and modulation are dynamic processes that lead to the sequential recruitment and accumulation of immune cells around the trapped Schistosoma egg, mediated by a local production of immune mediators, such as cytokines and chemokines . The granuloma induced by parasite eggs causes the confinement of the parasite antigens, thereby protecting the host tissue from their cytotoxic effect.…”
Section: Introductionmentioning
confidence: 99%